2007
DOI: 10.1210/me.2007-0067
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity Phosphatase 1 Knockout Mice Show Enhanced Susceptibility to Anaphylaxis but Are Sensitive to Glucocorticoids

Abstract: Dual specificity phosphatase DUSP1 (otherwise known as mitogen-activated phosphatase 1 or MKP-1) dephosphorylates MAPKs, particularly p38, and negatively regulates innate immunity. Recent studies have shown that the DUSP1 gene is transcriptionally up-regulated by glucocorticoids (GCs) and that the antiinflammatory action of GCs is impaired in DUSP1-/- mice. Here we show that GC-mediated dephosphorylation of ERK-1 and ERK-2 activated by IgE receptor cross-linking is unimpaired in bone marrow-derived mast cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 25 publications
2
56
0
Order By: Relevance
“…S8). Dexamethasone also inhibited TLR-stimulated cytokine production in DCs from control mice, consistent with reports in other cell types (27), but, similar to its effect on P-p38, here inhibition was only partially dependent on MKP-1 (Fig. 5).…”
Section: Mkp-1 Is Essential For Anti-ac Igm-mediated Suppression Of Isupporting
confidence: 89%
“…S8). Dexamethasone also inhibited TLR-stimulated cytokine production in DCs from control mice, consistent with reports in other cell types (27), but, similar to its effect on P-p38, here inhibition was only partially dependent on MKP-1 (Fig. 5).…”
Section: Mkp-1 Is Essential For Anti-ac Igm-mediated Suppression Of Isupporting
confidence: 89%
“…GCs might have some direct antiinflammatory effects, or they might also act via the induction of other antiinflammatory proteins. This idea is supported by the prior finding that inhibition of protein synthesis in bone marrow-derived mast cells from Mkp1 -/-mice partly reverses the antiinflammatory effects of GCs (41).…”
Section: (E and F)mentioning
confidence: 54%
“…Other investigators reported increased mortality in Mkp-1 null mice challenged with Gram-positive bacterial infection, through the inactivation of JNK and p38 (56). Mkp-1 null mice have shown enhanced susceptibility to anaphylaxis, while maintaining sensitivity to glucocorticoids in bone marrow-derived mast cells from the same mice (32). However, MKP-1 in EC was presented as a novel and crucial mediator of the anti-inflammatory action of glucocorticoids (16).…”
Section: Discussionmentioning
confidence: 99%